Revisiting exercise-induced premature ventricular complexes as a prognostic factor for mortality in asymptomatic patients: A systematic review and meta-analysis - Iqbal, Mohammad; Putra, Iwan Cahyo Santosa; Kamarullah, William; Pranata, Raymond; Achmad, Chaerul; Karwiky, Giky; Pramudyo, Miftah; Goenawan, Hanna; Akbar, Mohammad Rizki; Kartasasmita, Arief Sjamsulaksan; Kim, Young Hoon (Frontiers in Cardiovascular Medicine, 2022)
Introduction Recent investigations suggest that premature ventricular complexes (PVCs) during an exercise test are associated with an elevated risk of mortality in asymptomatic individuals. However, given to the small number of studies included, the association between these two entities in the asymptomatic population remains obscure. Our aim was to evaluate this matter. Methods A comprehensive literature search was conducted utilizing several online databases up to April 2022. The study comprised cohort studies examining the relationship between EI-PVCs and all-cause (ACM) as well as cardiovascular mortality (CVM) in asymptomatic populations. To provide diagnostic values across the statistically significant parameters, we additionally calculated sensitivity, specificity, and area under the curve (AUC). Results A total of 13 studies consisting of 82,161 patients with a mean age of 49.3 years were included. EI-PVCs were linked to an increased risk of ACM (RR=1.30 (95% CI=1.18–1.42); P<0.001; I2=59.6%, P-heterogeneity<0.001) and CVM (RR=1.67 (95% CI=1.40–1.99); P<0.001; I2=7.5%, P-heterogeneity=0.373). Subgroup analysis based on the frequency of PVCs revealed that frequent PVCs were similarly related with a higher risk of ACM and CVM, but not infrequent PVCs. Moreover, diagnostic test accuracy meta-analysis showed that recovery phase EI-PVCs have a higher overall specificity than exercise phase EI-PVCs regarding our outcomes of interest. Conclusion EI-PVCs are correlated with higher risk of ACM and CVM. When compared to the exercise phase, the specificity of PVCs generated during the recovery period in predicting interest outcomes is higher. As a result, we propose that the exercise ECG be utilized on a regular basis in the middle-aged asymptomatic individuals to measure the frequency of PVCs and stratify the risk of mortality.